Factors associated with the treatment outcomes of pulmonary tuberculosis patients enrolled in TB-DOTS Centers in the City of Manila: a cross-sectional study - Caronongan, Eunice Andrea T.; Cuaresma, Eumir Andres I.; Lopez, Kharina Malaya Q.; Gloria, Mac Ardy J. (Manila : Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2025)
The Philippines is one of the top countries with the highest tuberculosis burden in the world. To address this, Directly Observed Treatment Short-course (DOTS) is the core framework used by the National Tuberculosis Control Program (NTP). However, despite efforts to ensure patient compliance in TB-DOTS centers, there are still thousands of cases resulting in unsuccessful outcomes.

This study aimed to describe and determine the factors associated with treatment outcomes among patients enrolled in TB-DOTS centers in the City of Manila for 2022–2024.

A quantitative retrospective cross-sectional study design was used. Data from TB-DOTS centers was requested from the NTP. All adult patients with pulmonary TB enrolled & assigned a treatment outcome in TB-DOTS centers in the City of Manila from 2022–2024 were included. Frequency statistics were used to describe patient characteristics and treatment outcomes. Multinomial logistic regression was used to analyze possible associations using adjusted relative risk ratio.

20,809 patients were included in the study. Likelihood of treatment completion was higher in patients who were female, older, retreatment cases, and under SLOR-FQR or ITR regimens; and lower in unemployed, diabetic, and drug-resistant patients. Treatment failure was positively associated with unemployment, higher age, HIV, drug-resistance, and retreatment; and negatively associated with SLOR-FQR. Likelihood of loss to follow-up was higher in patients with increasing age, HIV, and SSOR, SLOR-FQS, SLOR-FQR, and ITR regimens; and lower in patients who are unemployed and diabetic. Lastly, likelihood of death was positively associated with increasing age, HIV infection, TB drug resistance, and history of previous TB treatment; and negatively associated with SLOR-FQR.

A variety of patient characteristics were associated with different TB treatment outcomes. A patient-centered approach to treatment is necessary to address all possible hindrances to being cured, where those with characteristics associated with negative outcomes are given more attention.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, July 2025
Keywords: Tuberculosis -- Drug therapy -- Outcomes -- Directly observed treatment -- Philippines -- Manila; Treatment outcomes -- Pulmonary tuberculosis -- Cross-sectional studies -- Philippines